Academic Burnout and Problematic Smartphone Use During the COVID-19 Pandemic: The Effects of Anxiety and Resilience - Hao, Zejun; Jin, Liangyi; Huang, Jinzi; Lyu, Ruibo; Cui, Qian (Frontiers in Psychiatry, 2021)
Background: Academic burnout has been associated with problematic smartphone use. However, the mechanism underlying this relation has been inadequately explored during the COVID-19 pandemic. Materials and methods: A total of 748 Chinese undergraduate students were recruited in the study who were measured with their levels of academic burnout, anxiety, resilience and problematic smartphone use. Results: Our study showed that academic burnout significantly predicted problematic smartphone use both directly and indirectly via anxiety. By constructing a moderated mediation model, our study found resilience moderated the direct impact and the second half of the indirect path (between anxiety and problematic smartphone use); however, with the moderation effects of resilience, both the indirect impact of academic burnout on problematic smartphone use via anxiety became insignificant. Conclusions: Our findings brought additional evidence on the association between academic burnout and problematic smartphone use and significantly, suggested the potential solution to alleviate the influences.